Active Experience Shapes 10‐Month‐Old Infants' Understanding of Collaborative Goals. (8th May 2012) - Henderson, Annette M. E.; Wang, Ying; Matz, Lauren E.; Woodward, Amanda L.
<x xml:space="preserve">Abstract</x> Collaborative activities in which individuals coordinate their actions to attain a common goal play a fundamental role in our everyday lives. Evidence suggests that infants engage in collaborative activities before their first birthday; however, little is known about infants' understanding of collaborative action. Using a visual habituation paradigm, this research consists of two experiments designed to investigate whether 10‐month‐olds understand that the actions of collaborative partners are critical to the attainment of a common goal. The results of Experiment 1 suggest that 10‐month‐olds represent the actions of collaborating partners in terms of a common collaborative goal only after receiving active experience with a collaborative activity. Experiment 2 demonstrated that infants who received active experience with a collaborative activity viewed active engagement in a collaboration as being critical for an individual's actions to be interpreted as being directed towards a collaborative goal. Together, these findings demonstrate that 10‐month‐olds exhibit an understanding of the shared nature of collaborative goals after a highly salient experience with the activity. Identifying the effects of experience on infants' understanding of collaborative goals in a laboratory context provides insights into the role that experiences in their everyday lives might play in their understanding of collaboration.